Intussusception Secondary to Isolated Heterotopic Pancreas of Meckel’s Diverticulum (TAJ: Journal of Teachers Association, 2011)
Intussusception in the pediatric age group is usually idiopathic in origin, and in a small number of patients ranging from 2% to 12%, a pathological lesion as a leading point is identifiable. Of the variety of pathologcial lesions identified as leading points for intussusception, Meckel’s diverticulum is the most common but very rarely, isolated heterotopic pancreas is found within it.This is a case report of intussusception in an infant caused by an isolated heterotopic pancreas of the Meckel’s diverticulum. The literature on the subject is also reviewed.TAJ 2011; 24(1): 16-20